Body weight, gender and pregnancy affect enantiomer‐specific ketorolac pharmacokinetics. (14th May 2017) - Välitalo, Pyry A.; Kemppainen, Heidi; Kulo, Aida; Smits, Anne; van Calsteren, Kristel; Olkkola, Klaus T.; de Hoon, Jan; Knibbe, Catherijne A. J.; Allegaert, Karel
Abstract : Aims: Although ketorolac analgesia is linked only to the S‐enantiomer, there is limited information on the stereo‐selective pharmacokinetics of this agent. We studied the stereo‐selective pharmacokinetics of ketorolac in a pooled dataset of two studies, with women at delivery and 4–5 months postpartum, and males and nonpregnant females. Methods: Nonlinear mixed‐effect modelling was used to evaluate the stereo‐selective pharmacokinetics of ketorolac tromethamine after a single intravenous injection immediately after delivery ( n = 41), 4–5 months postpartum ( n = 8, paired), and in male ( n = 12) and nonpregnant female ( n = 14) subjects. All of the males and six of the nonpregnant females were recruited from another study, in which they were undergoing blood sampling for 24 h. All remaining cases underwent blood sampling for 8 h. Results: For both the R‐ and S‐enantiomers, body weight affected ketorolac clearance. In addition, clearance for both enantiomers was 36% [95% confidence interval (CI) 15%, 58%] higher in male than in female subjects of the same body weight, and 55% (95% CI 33%, 78%) higher in women at delivery than in nonpregnant women of the same body weight. Women at delivery also had a 27% (95% CI 8%, 46%) higher distribution volume than nonpregnant women. The proportional effects of the covariates were not significantly different for the two ketorolac enantiomers. Conclusions: Besides the anticipated impact of body weight on clearance, R‐ and S‐ketorolac clearance is increased in male subjects and in women at delivery. To reach an exposure equivalent to that in nonpregnant women, males should receive a 36% increased ketorolac dose and pregnant women a 55% increased dose, in addition to a dose adjustment by body weight.